2016
DOI: 10.1097/mat.0000000000000408
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension in the Era of Mechanical Circulatory Support

Abstract: Left heart disease (LHD) represents the most common cause of pulmonary hypertension (PH), and is associated with worse prognosis compared to LHD without PH. In addition, PH due to LHD may prevent patients from receiving heart transplantation, due to risk of perioperative right ventricular failure. Current literature lacks comprehensive descriptions and management strategies of PH due to LHD. In this review, we summarize the literature that is available to highlight the definition, pathogenesis, and prognosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…For others, for example, those with “fixed” pulmonary hypertension, durable LVAD support acts as a “bridge to candidacy” as it may allow reversal of the pulmonary hypertension to a level that is considered safe for heart transplantation. 56…”
Section: Impact Of Frailty On Vad Outcomesmentioning
confidence: 99%
“…For others, for example, those with “fixed” pulmonary hypertension, durable LVAD support acts as a “bridge to candidacy” as it may allow reversal of the pulmonary hypertension to a level that is considered safe for heart transplantation. 56…”
Section: Impact Of Frailty On Vad Outcomesmentioning
confidence: 99%
“…Concerning diastole, the left ventricle is stiffer than a failed unassisted ventricle, due to the "reverse-remodelling" operated by the LVAD (47). The systemic and pulmonary circulation are adjusted to reproduce a relatively lower peripheral resistance [due to pharmacological treatment (48)] and a slightly higher pulmonary resistance, observed in some LVAD patients (49). In addition, some tuning of the control mechanisms that drive the adaptation of the cardiovascular system to exercise are also performed (44).…”
Section: Description Of the Cardiorespiratory Simulatormentioning
confidence: 99%
“…22 If medical therapy fails to achieve acceptable pulmonary hemodynamics and primary pulmonary causes of PH have been excluded, an LVAD should be considered to maximize left ventricular unloading and pulmonary vascular remodelling. 23 Most studies have shown significant reduction in pulmonary pressures post LVAD placement. 23,24 Hemodynamic reevaluation is performed at 3-6 months after LVAD placement to ascertain PH reversibility.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%
“…23 Most studies have shown significant reduction in pulmonary pressures post LVAD placement. 23,24 Hemodynamic reevaluation is performed at 3-6 months after LVAD placement to ascertain PH reversibility. A small number of single-centre studies have successfully used phosphodiesterase-5 inhibitors to reduce PH and facilitate candidacy for HTx without LVAD placement.…”
Section: Pulmonary Hypertensionmentioning
confidence: 99%